2016
DOI: 10.1111/cea.12829
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomic analysis of house dust mite antigens reveals distinct classes of dominant T cell antigens according to function and serological reactivity

Abstract: BACKGROUND House dust mite (HDM) allergens are a common cause of allergy and allergic asthma. A comprehensive analysis of proteins targeted by T cells, which are implicated in the development and regulation of allergic disease independent of their antibody reactivity, is still lacking. OBJECTIVE To comprehensively analyze the HDM-derived protein targets of T cell responses in HDM-allergic individuals, and investigate their correlation with IgE/IgG responses and protein function. METHODS Proteomic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Using predicted peptide binding as a preselection criterion to decrease the number of peptides to screen for T cell epitope identification is less thorough than using overlapping peptides and may therefore increase the risk of missing T cell-reactive peptides. However, it has been reported that it is a reliable approach to identify the vast majority of T cell epitopes [28,29], and it has been successfully used in several allergen systems, including Timothy grass [11], German cockroach [30], house dust mite [31], and others [32], to perform large-scale epitope identification studies. Therefore, the decision between using overlapping and predicted peptides is likely dictated by the size and number of allergens studied as well as the amount of cells available from the clinical cohort.…”
Section: Overlapping Versus Predicted Peptidementioning
confidence: 99%
“…Using predicted peptide binding as a preselection criterion to decrease the number of peptides to screen for T cell epitope identification is less thorough than using overlapping peptides and may therefore increase the risk of missing T cell-reactive peptides. However, it has been reported that it is a reliable approach to identify the vast majority of T cell epitopes [28,29], and it has been successfully used in several allergen systems, including Timothy grass [11], German cockroach [30], house dust mite [31], and others [32], to perform large-scale epitope identification studies. Therefore, the decision between using overlapping and predicted peptides is likely dictated by the size and number of allergens studied as well as the amount of cells available from the clinical cohort.…”
Section: Overlapping Versus Predicted Peptidementioning
confidence: 99%
“…The ability to make recombinant D. pteronyssinus homologues of these components from the information in the genome not only opens up these investigations to studies in the many more regions where people are substantively or almost exclusively sensitized by D. pteronyssinus, but also to the possibility that investigators in these regions are more interested in making authenticable assessments. The T-cell responses of house dust mite-allergic subjects from Europe and America made to peptides representing predicted epitopes of many of these proteins showed that they did not induce substantive T-cell responses compared to the responses induced by the high IgE-binding components authenticated earlier with quantitative analyses [6], Why would you want to sequence the house dust mite genome? Randall et al [1] help explain this in an analysis of their assembly of the genomic sequence of Derma tophagoides pteronyssinus.…”
mentioning
confidence: 99%
“…IgE binding to Der p 14 and a small group of other apparently minor IgE-binding proteins has been associated with an additional propensity of house dust mite-allergic children to develop asthma [21], and it has also been found to be one of the most stimulatory allergens as assessed by the T-cell epitope study by Oseroff et al [6]. Antibodies produced to recombinant Der p 14 have not only revealed the presence of a Der p 14-like molecule in house dust mite eggs, which would be expected to be a vitellogenin known to belong to this type of protein, but also a protein in the bodies of male mites that correspond to the related lipid transporter apolipophorin [22].…”
mentioning
confidence: 99%
See 2 more Smart Citations